AN INNOVATIVE METHODOLOGY FOR EVALUATING AND ASSESSING B1-LEVEL STUDENTS’ READING SKILLS IN ENGLISH LESSONS THROUGH MOBILE APPLICATIONS (INTERNATIONAL CONFERENCE ON MEDICINE, SCIENCE, AND EDUCATION, 2025)
The integration of digital technologies in foreign language teaching has led to significant innovations in evaluation and assessment methodologies. This paper examines how mobile applications can be effectively used to evaluate and assess the reading skills of B1-level learners in English lessons. The study focuses on formative and summative assessment strategies within a mobile-assisted language learning (MALL) framework. The paper also explores how adaptive reading platforms and mobile testing tools contribute to individualized feedback, motivation, and data-driven evaluation. Findings suggest that mobile-based assessment supports continuous learning, fosters learner autonomy, and enhances the validity of reading skill evaluation in English language teaching.